Do sports compression garments alter measures of peripheral blood flow? A systematic review with meta-analysis - O`Riordan, S. F.; Bishop, D. J.; Halson, S. L.; Broatch, J. R. (Sports Medicine, 2023)
Background: One of the proposed mechanisms underlying the benefits of sports compression garments may be alterations in peripheral blood flow. Objective: We aimed to determine if sports compression garments alter measures of peripheral blood flow at rest, as well as during, immediately after and in recovery from a physiological challenge (i.e. exercise or an orthostatic challenge). Methods: We conducted a systematic literature search of databases including Scopus, SPORTDiscus and PubMed/MEDLINE. The criteria for inclusion of studies were: (1) original papers in English and a peer-reviewed journal; (2) assessed effect of compression garments on a measure of peripheral blood flow at rest and/or before, during or after a physiological challenge; (3) participants were healthy and without cardiovascular or metabolic disorders; and (4) a study population including athletes and physically active or healthy participants. The PEDro scale was used to assess the methodological quality of the included studies. A random-effects meta-analysis model was used. Changes in blood flow were quantified by standardised mean difference (SMD) [± 95% confidence interval (CI)]. Results: Of the 899 articles identified, 22 studies were included for the meta-analysis. The results indicated sports compression garments improve overall peripheral blood flow (SMD = 0.32, 95% CI 0.13, 0.51, p = 0.001), venous blood flow (SMD = 0.37, 95% CI 0.14, 0.60, p = 0.002) and arterial blood flow (SMD = 0.30, 95% CI 0.01, 0.59, p = 0.04). At rest, sports compression garments did not improve peripheral blood flow (SMD = 0.18, 95% CI - 0.02, 0.39, p = 0.08). However, subgroup analyses revealed sports compression garments enhance venous (SMD = 0.31 95% CI 0.02, 0.60, p = 0.03), but not arterial (SMD = 0.12, 95% CI - 0.16, 0.40, p = 0.16), blood flow. During a physiological challenge, peripheral blood flow was improved (SMD = 0.44, 95% CI 0.19, 0.69, p = 0.0007), with subgroup analyses revealing sports compression garments enhance venous (SMD = 0.48, 95% CI 0.11, 0.85, p = 0.01) and arterial blood flow (SMD = 0.44, 95% CI 0.03, 0.86, p = 0.04). At immediately after a physiological challenge, there were no changes in peripheral blood flow (SMD = - 0.04, 95% CI - 0.43, 0.34, p = 0.82) or subgroup analyses of venous (SMD = - 0.41, 95% CI - 1.32, 0.47, p = 0.35) and arterial (SMD = 0.12, 95% CI - 0.26, 0.51, p = 0.53) blood flow. In recovery, sports compression garments did not improve peripheral blood flow (SMD = 0.25, 95% CI - 0.45, 0.95, p = 0.49). The subgroup analyses showed enhanced venous (SMD = 0.67, 95% CI 0.17, 1.17, p = 0.009), but not arterial blood flow (SMD = 0.02, 95% CI - 1.06, 1.09, p = 0.98). Conclusions: Use of sports compression garments enhances venous blood flow at rest, during and in recovery from, but not immediately after, a physiological challenge. Compression-induced changes in arterial blood flow were only evident during a physiological challenge.